FORMATION AND DEVELOPMENT OF VOCATIONAL EDUCATION - Yorkin Shukurov (Galaxy International Interdisciplinary Research Journal, 2021)
The success of the educational process depends not only on its form but also on the effectiveness of the methods used, which occupies one of the key positions in the theory of education. A method is Greek for metros, which means way, research. the teaching method is a joint activity of the teacher and students aimed at achieving a specific goal in the learning process. Teaching methods are the ways to achieve the goals of teaching, as well as the theoretical and practical orientation of the teaching material.